Microevolution rather than large genome divergence determines the effectiveness of legume–rhizobia symbiotic interaction under field conditions - Jozefkowicz, Cintia; Brambilla, Silvina Maricel; Frare, Romina Alejandra; Stritzler, Margarita; Puente, Mariana Laura; Piccinetti, Carlos Fabian; Soto, Gabriela Cinthia; Ayub, Nicolás Daniel (2017)
Despite the vast screening for natural nitrogenfixing isolates by public and private consortia, no significant progresses in the production of improved nitrogenfixing inoculants for alfalfa production have been made in the last years. Here, we present a comprehensive characterization of the nitrogen-fixing strain Ensifer meliloti B399 (originally named Rhizobium meliloti 102F34), probably the inoculant most widely used in alfalfa production since the 1960s. Complete nucleotide sequence and genome analysis of strain B399 showed that the three replicons present in this commercial strain and the model bacterium Ensifer meliloti 1021 are extremely similar to each other in terms of nucleotide identity and synteny conservation. In contrast to that observed in B399-treated plants, inoculation of plants with strain 1021 did not improve nitrogen content in different alfalfa cultivars under field conditions, suggesting that a small genomic divergence can drastically impact on the symbiotic phenotype. Therefore, in addition to the traditional screening of natural nitrogen-fixing isolates, the genome engineering of model strains could be an attractive strategy to improve nitrogen fixation in legume crops.